Pengaruh Deviden Per Share, Return On Equity, Net Profit Margin, Return On Investment, Dan Return On Assets Terhadap Harga Saham Pada Perusahaan Real Estate Dan Property Terdaftar Di BEI Periode 2017-2020 - Heri Mohammad Setiawan; Muhammad Agus Salim; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The Real Estate and Property sector is perhaps the main area for the monetary development of the Indonesian State. Creating assets with various comfortable structures with the aim that it can also influence Indonesia's financial development. The population of this study is Real Estate and Property Companies listed on the Indonesia Stock Exchange from 2017 to 2020. The method used in this test is purposive sampling, which depends on qualification. The scientific tool used is multiple linear regression. Test indicate that the DPS variable has a large and positive impact on stock prices in real estate and property companies on the Indonesia Stock Exchange. The ROE variable has a positive and insignificant effect on stock prices in real estate and property companies on the Indonesia Stock Exchange. The NPM variable has a negative and insignificant impact on stock prices in real estate and property companies on the Indonesia Stock Exchange. The return on investment  capital variable has a negative and insignificant impact on stock prices in real estate and property companies on the Indonesia Stock Exchange. The ROA variable has a positive and insignificant effect on stock prices in real estate and property companies at the Indonesian Stock Exchange. Keywords: Stock Exchange, Deviden Per Share, Return On Equity, Net Profit Margin, Return On Investment, dan Return On Assets.